Strategy of location and control of FACTS devices for enhancing power quality - Mahdad, B.; Bouktir, T.; Srairi, K. (MELECON 2006 - 2006 IEEE Mediterranean Electrotechnical Conference, 2006)
In the practical installation of FACTS in the power system, there are three common requirements as follows: what kinds of FACTS devices should be installed; where in the system should they be placed; and how much capacity should it have. This paper focuses on the first two of these requirements. Choosing the type of FACTS devices and deciding the installation location and control of FACTS. We presented a simple algorithm based in heuristic and practical rules to seek the optimal location of two types of FACTS, shunt compensation 'SVC' and series compensation 'TCSC'. The system loadability and loss minimization are applied as a measure of power system performance. Results show the impact of optimal operating points of FACTS (SVC and TCSC) devices under various conditions of power system. The proposed methodology to install and operate FACTS devices properly is verified on the 9-bus system where FACTS devices operated under normal and abnormal condition